Wiki for the Academic Writing Classroom - Nik Aloesnita, Nik Mohd Alwi; Zailin Shah, Yusoff (2010)
Wiki is a web 2.0 tool the offers a platform for collaboration, co-production of text, and interaction throughout writing processes (e.g Bruns & Humphreys, 2005). Its "transparency and openness" (Carr, et al., 2007:280) due to its editable features, lends itself to collaborative, process writing approach. While studies have revealed that wiki is useful tool to be used to promote second language writing (e.g Zailin Shah, 2010), its used in writing classroom s is underexplored. As such, the proposed tutorial aims to offer participants with more insides into the used of wiki for teaching and learning in the Academic Writing classroom. The session will be divided into three parts. The first part is an introduction to the wiki software including the description of how wiki may serve as the medium for language teaching and learning, particularly in promoting collaborative second language writing. This will also include the theoretical framework that supports its applications. The second part involves presenters demonstrating the processes of creating and managing wikis. The wiki features such as editing, monitoring, uploading files and tracking changes will also be discussed. In the third and final part of the session, the presenter will share their experiences with the participants some of the ways in which wiki has been implemented in their academic writing classroom specifically for collaborative writing and teacher feedback. By the end of the session, the participant will not only able to understand wiki theoretically but also pedagogically (practically).